Exploring Arabic Reading and Speaking Skills through Picture Storybooks: Study Literature Review - Safitriani, Ida; Khasairi, Moh.; Alfan, Muhammad; Ayni, Alisia Budi Nor (Mantiqu Tayr: Journal of Arabic Language, 2025)
The low proficiency in Arabic reading and speaking among students is often attributed to monotonous teaching methods and a lack of visual learning media. This study explores the pedagogical potential of picture storybooks as a multimodal solution to support Arabic language learning at the elementary and secondary levels. The research aims to analyze how picture storybooks influence vocabulary acquisition, sentence structure comprehension, reading literacy, and speaking fluency. Using a qualitative library research approach, data were gathered from peer-reviewed journals, books, and academic reports published within the last five years. The findings indicate that integrating visual and verbal elements through picture storybooks helps students understand vocabulary in context, builds confidence in speaking, and increases motivation to engage with reading. This approach supports key theories in language learning, including Dual Coding Theory, Multimodal Learning, Krashen’s Input Hypothesis, and Vygotsky’s Sociocultural Theory. All of which emphasize language learning as a meaning-focused, context-rich, and socially mediated process. The study concludes that picture storybooks serve as an effective instructional tool for Arabic language education by bridging cognitive, affective, and linguistic domains. It recommends further empirical studies in real classroom settings to evaluate the long-term impact of this medium across different learner profiles and proficiency levels.